2015
DOI: 10.1007/lrsp-2015-4
|View full text |Cite
|
Sign up to set email alerts
|

The Solar Cycle

Abstract: The solar cycle is reviewed. The 11-year cycle of solar activity is characterized by the rise and fall in the numbers and surface area of sunspots. A number of other solar activity indicators also vary in association with the sunspots including; the 10.7 cm radio flux, the total solar irradiance, the magnetic field, flares and coronal mass ejections, geomagnetic activity, galactic cosmic ray fluxes, and radioisotopes in tree rings and ice cores. Individual solar cycles are characterized by their maxima and min… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
505
1
15

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 829 publications
(608 citation statements)
references
References 205 publications
16
505
1
15
Order By: Relevance
“…Since the original RGO series was terminated in 1976, its extension with SOON (Solar Observing Optical Network) data (Neidig et al 1998) may have a transition inhomogeneity related to the reported group areas (Lockwood et al 2014;Hathaway 2015). However, this transition does not affect the present analysis, where we only consider the number and position of spot groups, not their sizes.…”
Section: Datamentioning
confidence: 97%
See 1 more Smart Citation
“…Since the original RGO series was terminated in 1976, its extension with SOON (Solar Observing Optical Network) data (Neidig et al 1998) may have a transition inhomogeneity related to the reported group areas (Lockwood et al 2014;Hathaway 2015). However, this transition does not affect the present analysis, where we only consider the number and position of spot groups, not their sizes.…”
Section: Datamentioning
confidence: 97%
“…The time-latitude evolution of sunspot occurrence, known as the Maunder butterfly diagram, is one of the most spectacular manifestations of the cyclic variability of solar activity, resulting from the action of the solar dynamo in the Sun's convection zone (Charbonneau 2010;Hathaway 2015). With the butterfly diagram, we can study the detailed evolution of the latitude distribution of sunspots and, thus, the dynamo wave propagation (e.g., Newton & Milsom 1955;Carbonell et al 1993;Pulkkinen et al 1999;Li et al 2002;Ballester et al 2005;Berdyugina et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These processes are crucial for the evolution of the solar cycle. On the latter, we refer the reader to the Living Review by Hathaway (2010).…”
Section: Modelling the Evolution Of Ars From Emergence Through Decaymentioning
confidence: 99%
“…However, SN series cannot be internally verified, and no selfconsistency checks are available beyond some non-strict empirical relations between the length and the amplitude of solar cycle (Waldmeier 1935;Hathaway 2015) or between the number of sunspots and groups (Friedli 2017). Accordingly, it is hardly possible to assess the reliability of different series from the sunspot data alone.…”
Section: Introductionmentioning
confidence: 99%